Cortical reinstatement in the visual associative memory network is compromised by early tau in normal older adults. (December 2021) - Mormino, Elizabeth C.; Trelle, Alexandra N.; Hunt, Madison; Tran, Tammy; Carr, Valerie A.; Toueg, Tyler; Deutsch, Gayle; Harrison, Marc; Sha, Sharon; Rutt, Brian S.; Kerchner, Geoffrey A.; Wagner, Anthony D.
Abstract: Background: The structure and computations associated with specific hippocampal subfields decline in aging and are also initial sites of Alzheimer's disease pathology. The degree to which age‐associated changes in hippocampal‐dependent memory are driven by early AD pathology among older normal adults remains unclear. Method: We enrolled one hundred ninety‐nine clinically unimpaired (CU) older individuals into the Stanford Aging and Memory Study (SAMS, 117 Female, mean age= 68.9±6.2). Participants completed a lumbar puncture to collect cerebrospinal fluid (CSF), high‐resolution fMRI (at 3T) during a visual associative memory paradigm, and ultra high‐resolution structural MRI (at 7T) to assess MTL subregion integrity, as well as extensive cognitive assessment. Data collection is complete, and analysis of fMRI and 7T structural data of the 199 participants is currently underway. To examine neuronal computations underlying hippocampal dependent memory, we focused on fMRI metrics in a subset of 78 participants that quantify cortical reinstatement (the degree to which voxelwise patterns of activation during retrieval match activation patterns during encoding) in two a priori regions known to be important for visual associative memory (ventral temporal cortex, VTC; and angular gyrus, ANG). Additionally, we extracted univariate fMRI signal from the hippocampus during successful retrieval. Finally, hippocampal thickness from CA1 in a subset of 77 participants was manually delineated on 7T scans, and CSF was processed with Lumipulse to measure Ab42 :Ab40 ratio and p‐tau181. Result: Elevated p‐tau181 was associated with worse performance on the fMRI‐scanned visual associative memory task (Figure A), reduced cortical reinstatement strength in both VTC (r = ‐0.25, p = .027, Figure B) and ANG (r = ‐0.22, p = .048), as well as reduced CA1‐SRLM thickness (r = ‐0.32, p = .004, Figure C). Although Ab42 :Ab40 ratios were related to p‐tau181, they were not independently associated with neuronal indices of hippocampal‐dependent memory. Conclusion: CU with evidence of early tau abnormalities show worse hippocampal‐dependent memory and differences in fMRI and structural measurements in regions critical for successful associative memory. Initial consequences of AD pathology target specific hippocampal‐cortical circuits, and this is measurable using advanced MRI techniques.